Resetting the International Monetary (Non)System - Antonio Ocampo, José (Oxford University Press, 2021)
This book provides an analysis of the global monetary system and the necessary reforms that it should undergo to play an active role in the twenty-first century. As its title indicates, its basic diagnosis is that it is an ad hoc framework rather than a coherent system—a ‘non-system’—which evolved after the breakdown of the original Bretton Woods arrangement in the early 1970s. The book places a special focus on the asymmetries that emerging and developing countries face within the current system, and therefore on the development dimensions of the global monetary system and of global monetary reform. The book proposes a comprehensive yet evolutionary reform of the system that includes: (i) provision of international liquidity through a system that mixes the multi-currency arrangement with a more active use of the IMF’s Special Drawing Rights (SDRs), the only true global currency that has been created; (ii) stronger mechanisms of macroeconomic policy cooperation, including greater cooperation in exchange rate management, and freedom to manage capital flows as a complement to counter-cyclical macroeconomic policy and other instruments of financial regulation; (iii) additional automatic balance-of-payments financing facilities, and the complementary use of swap and regional arrangements; (iv) a multilateral sovereign debt workout mechanism; and (v) major reforms of the system’s governance, based on a more representative apex organization, more equitable participation of emerging and developing countries in decision-making, and a network of global, regional, inter-regional, and sub-regional organizations.